Procedural monsters: rhetoric, commonplace and 'heroic madness' in video games. Issue 3 (3rd July 2018) - Grimwood, Tom
ABSTRACT: This paper draws on Ian Bogost's argument that video games constitute a form of 'procedural rhetoric', in order to re-examine the representation of heroic madness First-Person-Shooter games. Rejecting the idea that games attempt to recreate the experience of madness to the player through linear representation, the paper instead identifies two persistent commonplace figures which appear within the genre: the monstrous double, and the reaching tentacle. While Bogost's notion of procedural rhetoric allows analysis to move away from the more facile interpretations of gameplay, the paper argues that these figures also demand an account of the commonplace itself – the rhetorical 'topic' – which links the technical structure of gaming procedures with the tropes and figures that enable them to make sense within their wider cultural context and tradition. While the figures of the double and the tentacle purposefully draw on existing tropes and processes associated with the cultural meanings of mental health, a rhetorical analysis of their use of commonplaces suggests that they are not simply recycling older clichés, but constitute a creative 'reobjectification' of madness.